A New Approach to Refugee's Welfare through the Role of Community: Case Study of Refugee's Community Centre in Sewon - Anak Agung Istri Diah Triceseria; Nurul Azizah Zayda; Rizka Fiani Prabaningtyas (Institute of International Studies, 2015)
The role of state actor in refugee protection is seriously limited by the “nationalism” nature of a nation-state. In particular, there has been a lack of attention from Indonesia as implied by non-ratifying choice taken by the government. The problem here with this approach is, refugee’s rights are viewed as entitlement from state and should conform with the state’s interest. Thus, there needs to be a new approach in pursuing a refugee protection regime. This paper shifts the focus from the role of state to the roles played by other actors. This paper gives a particular focus on Refugee Community Housing in Sewon, Daerah Istimewa Yogyakarta. The Community Housing is an initiative from International Organization for Migration (IOM) which provides temporary settlement as well as living allowance for refugees. Our preliminary study found that the coordination among IOM, Jesuit Refugee Service (JRS)–an international NGO working to assist refugees, and Immigration Office of Yogyakarta—has to some extent demonstrated a better service and treatment to refugees than state’s philanthropy in general. Some limitations remains exist, but overall, community housing provides a foundation for a civil society-based refugee protection.